Portinari, poeta de imensidões - Cozendey, Ana Carla Bicalho (1998)
In the work of the painter Cândido Portinari, poetry, if one takes the term in the wide sense of a phenomenon which may be applied to different art-forms, is evident as a mark that unites his great range of technique and stylistic tendencies. With the methodologi- cal support of Gaston Bachelard's phenomenology, emphasizing material imagination linked to the four basic elements of water, earth, fire and air, the dissertation approaches the poetic imagination of the painter which creates poetic images strongly linked to the earth. Following these images, one experiences a sense of space expanding and concen- trating, which may be defined as central to Portinari's poetry. In the relationship between the intensified external and internal spaces, vastness is encountered.